A Micellar Liquid Chromatographic Method for the Determination of Azosemide in Solubilized System. Issue 6 (10th August 2017) - Malvia, Hitesh; Sharma, Ashok; Sharma, Pratibha; Mishra, Ritesh
Abstract: A simple micellar liquid chromatographic method was developed and validated for the determination of azosemide (AZS). The method incorporates surfactant media beyond the critical micellar concentration level for the study of AZS in bulk and pharmaceutical dosage forms. Quantitation was achieved through UV detection. An interpretive optimization procedure was used to ascertain the optimum conditions based on the accurate description of the retention and shape of the chromatographic peak for quantification of AZS, viz., selection of surfactants, pH of buffer solution, concentration of surfactant and selection of solvent etc. The method was successfully validated as per the requirements of the international Council for Harmonisation (ICH) guidelines and showed excellent linearity within the limits of detection and limit of quantitation. The method was linear over the concentration range 0.001–0.2 mg ml −1 with regression coefficient ( r 2 ) 0.999. The proposed method was successfully applied for ascertaining the stability and determination of AZS under different stressed conditions viz., basic, acidic, oxidative, photolytic, and thermal degradation. The method elicited good selectivity, repeatability, linearity and sensitivity of the validated parameters. Recoveries obtained were in a range of 98.90–99.58%. The method allows accurate and reliable determination of AZS for drug stability assays in pharmaceutical investigations using environmentally friendly materials.